Melatonin is a potential target for improving horticultural crop resistance to abiotic stress - Zhao, C.; Nawaz, G.; Cao, Q.; Xu, T.
Crop yield and quality are greatly affected by abiotic stresses, such as salinity, high and low temperature, drought and heavy metals, which pose major threat to human survival and development. Melatonin (N-acetyl-5-methoxytryptamine), an indoleamine that widely exists in plants and animals, is a bio-stimulator involved in the regulation of plant growth and productivity. It scavenges oxidative stress caused by reactive oxygen species, potentially increases photosynthetic rate, chlorophyll content and is involved in the regulation of auxin, salicylic acid and nitric acid levels in plants. Genomic studies have explored melatonin-induced signaling, enzymes, transcription factors and the expression of stress- and metabolism-related genes in plants. Although much has been determined about the function of melatonin in plants, its role in inducing tolerance to abiotic stress in crop species is largely unknown. This review focuses on a comprehensive study of melatonin-induced physiological and molecular events in horticultural crops, which are important to the development of tolerance and enhancement of productivity in horticultural crops under abiotic stress conditions.
Keywords: MELATONIN; HORTICULTURAL CROP; RESISTANCE; ABIOTIC STRESS